Training soft skills in Russian language classes with foreign students of economic specialties - Natal’ya O. Il’ina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the problem of soft skills development when working with foreign students in the course of Russian as a foreign language. It is known that soft skills are currently being actively introduced into the learning process at all levels of education. In this regard, it is necessary to include tasks for the development of soft skills in the educational process of foreign students in classes on the scientific style of speech and the language for specialty purposes. The purpose of this study is to analyze methodological approaches and develop tasks that meet the communicative needs of foreign students receiving Russian education and, therefore, acquiring soft skills in the main subjects of their field of study. The research offers options for tasks for soft skills development for foreign students studying economics. The work also analyzes the importance of teamwork, which helps to create the most comfortable atmosphere that facilitates free exchange of opinions and the active participation of all students in classroom activities. The paper draws attention to one of the most effective techniques for developing soft skills, namely, gaming technology. With the help of an educational game in classes on Russian as a foreign language, you can solve a number of complex problems that contribute to the development of the skills in question. In conclusion, the author focuses on the fact that despite the absence of Soft Skills competencies in the list of competencies listed in the federal state requirements for Russian as a foreign language, it is necessary to look for methodological techniques and forms of work, develop exercises and tasks for the formation and development of soft skills, so as dictated by the communicative needs of foreign students receiving education in the Russian Federation.